Viscous and viscoelastic stress states at the calving front of Antarctic ice shelves. Issue 73 (23rd May 2016) - Christmann, Julia; Plate, Carolin; Müller, Ralf; Humbert, Angelika
ABSTRACT: Calving mechanisms are still poorly understood and stress states in the vicinity of ice-shelf fronts are insufficiently known for the development of physically motivated calving laws that match observations. A calving model requires the knowledge of maximum tensile stresses. These stresses depend on different simulation approaches and material models. Therefore, this study compares results of a two-dimensional (2-D) continuum approach using finite elements with results of a one-dimensional (1-D) beam model elaborated in Reeh (1968). A purely viscous model, as well as a viscoelastic Maxwell model, is applied for the 2-D case. The maximum tensile stress usually appears at the top surface of an ice shelf. Its location and magnitude are predominantly influenced by the thickness of the ice shelf and the height of the freeboard, the traction-free part at the ice front. More precisely, doubling the thickness leads to twice the stress maximum, while doubling the freeboard, based on changes of the ice density, results in an increase of the stress maximum by 61%. Poisson's ratio controls the evolution of the maximum stress with time. The viscosity and Young's modulus define the characteristic time of the Maxwell model and thus the time to reach the maximum principal stress.